Pandangan Agustinus dari Hippo tentang Krisis Ekologis dalam Relasi Manusia dan Alam - Yosef Valdo Leso; Mensivansinus Hardi Yanto; Albertus Gumin (Pusat Riset dan Inovasi Nasional, 2026)
The contemporary ecological crisis demonstrates an imbalance in the relationship between humans and nature that is not only ecological, but also theological and moral. This article aims to analyze the ecological crisis from the perspective of Augustine of Hippo through the concepts of free will (liberum arbitrium) and the order of love (ordo amoris), as well as their relevance to the relationship between humans and nature. This study employs a qualitative approach using the library research method. The primary data sources are secondary literature, namely books and academic studies discussing Augustine’s philosophical and theological thought, supported by journal articles, Church documents, and contemporary ecotheological studies. The data were analyzed using descriptive-analytical and hermeneutic methods. The results of the study indicate that the ecological crisis originates from the disorientation of human will influenced by excessive self-love, which gives rise to an anthropocentric and exploitative attitude toward nature. From Augustine’s perspective, the restoration of the relationship between humans and nature requires an order of love directed toward God as the highest good. Therefore, the ecological crisis is understood as a spiritual crisis that demands an inner transformation of humanity in establishing an ethical relationship with all creation.